Assessment of Instructional Labor Support Behaviors among Laboring Women at Teaching Hospitals in Hilla City - Khairi, suhad; Mukeef, suad (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: The aim of this study to assess instructional labor support behaviors among laboringwomen in teaching hospitals in Hilla city.Methodology: A descriptive analytic study was concluded to select a sample purposely of one hundredmultipara laboring women in maternity hospital in Hilla city and data was collected throughquestionnaire form during February (1st to March 30th) 2014. A descriptive statistical method was usedto analyze the data.Results: The result showed that the highest percentage of study sample was at age (20-24) years, mostof them was house wife, more than third graduate from primary school, and more than half of themlived in rural area, (86%) of study sample delivered normal delivery, and (47%) of them their babieswere healthy, regarding instructional labor support behaviors, the highest mean of score refer toinstruction with eye to eye contact with persons who provide support, use open mouth (glottis) pushingand follow urges to push and rise the baby to let mother see her baby's gender.Recommendations: The result of this study indicated need for providing all midwifery school withlabor support behaviors, revising clinical guideline and efficient updating training to all staff and giverole to family to share in labor support behaviors